Survivorship of Trabecular Metal Anchored Glenoid Total Shoulder Arthroplasties. Issue 3 (September 2016) - Styron, Joseph F.; Marinello, Patrick G.; Peers, Sebastian; Seitz, William H.
Abstract : Trabecular metal anchored glenoids (TMAGs) were developed to counter the pervasive problem of component loosening at the bone-cement interface in total shoulder arthroplasty. Increased failure rates associated with the glenoid component have been previously reported due to increased rates of glenoid failures. Our hypothesis was that in our patients, the failure rate of TMAG implants is similar to or less than reported failure rates of traditional all polyethylene glenoid components. A medical chart review of 66 consecutive patients treated with a TMAG total shoulder replacement was conducted including clinical and radiographic follow-up. Paired t test analyses were used to compare the patients' preoperative and postoperative shoulder range of motion. Patients on average had 50.2 months of clinical follow-up available. Although the radiographs of several patients demonstrated focal areas of lucency, none of the patients demonstrated evidence of glenoid loosening. Glenoid component failure was a rare occurrence, happening only once in the 66 patients (1.5%). The patient with a glenoid fracture sustained that complication 6 years after her index total shoulder replacement. She was the only patient in the series who required revision surgery. Most patients experienced significant improvements in their shoulder range of motion, improving forward flexion from 73.7 to 144.2 degrees ( P <0.0001), internal rotation from L5 to T8 ( P <0.0001), and external rotation 12.8 to 48.9 degrees ( P <0.0001). With improved implant design and meticulous surgical technique, recent iterations of TMAG components do not produce excessive failure rates but result in significant functional improvements.